Perceptions of European medical staff on the facilitators and barriers to physical closeness between parents and infants in neonatal units. (24th April 2016) - Dykes, F; Thomson, G; Gardner, C; Hall Moran, V; Flacking, R
Abstract: Aim: Studies have provided insights into factors that may facilitate or inhibit parent–infant closeness in neonatal units, but none have specifically focused on the perspectives of senior neonatal staff. The aim of this study was to explore perceptions and experiences of consultant neonatologists and senior nurses in five European countries with regard to these issues. Methods: Six small group discussions and three‐one‐to‐one interviews were conducted with 16 consultant neonatologists and senior nurses representing nine neonatal units from Estonia, Finland, Norway, Spain and Sweden. The interviews explored facilitators and barriers to parent–infant closeness and implications for policy and practice, and thematic analysis was undertaken. Results: Participants highlighted how a humanising care agenda that enabled parent–infant closeness was an aspiration, but pointed out that neonatal units were at different stages in achieving this. The facilitators and barriers to physical closeness included socio‐economic factors, cultural norms, the designs of neonatal units, resource issues, leadership, staff attitudes and practices and relationships between staff and parents. Conclusion: Various factors affected parent–infant closeness in neonatal units in European countries. There needs to be the political motivation, appropriate policy planning, legislation and resource allocation to increase measures that support closeness agendas in neonatal units.